Practitioners' Perception Toward AIS Course Content Offered by Malaysian Universities (Malaysian Management Journal, 1999)
The purpose of this study is to determine the degree of importance of each topic included in the Accounting Information Systems (A IS) course from the practitioners' point of views. This study was motivated by the increasing progress in information technology which proposed to re-examine the AIS course in order to meet the expectations and requirements of the profession. Three hundred and forty (340) questionnaires were sent to three different groups of companies namely public accounting firms, industry and commerce, and banking and finance. The response rate received is 22.35%. Respondents' opinions on the importance of AIS topics were measured using a five-point Liken scale. Results from the mean analysis showed that practitioners in Malaysia perceived all AIS topics listed as important. However, results from ANOVA analysis indicated that .five ( 5) topics were perceived significantly different among the three groups of practitioners. The five topics are general concept of accounting information systems, procurement cycle, application software, entity-relationship diagram and programming languages. Further analysis using Scheffe test indicated that procurement cycle and entity-relationship diagram topics differ significantly between Industry and Commerce and Banking and Finance. Public Accounting Finns and Industry and Commerce differ significantly in the application software topics. There were significant differences between all the three groups in programming languages.